2014
DOI: 10.1080/14786435.2014.916428
|View full text |Cite
|
Sign up to set email alerts
|

Hidden order behaviour in URu2Si2(A critical review of the status of hidden order in 2014)

Abstract: Throughout the past three decades the hidden order (HO) problem in URu 2 Si 2 has remained a "hot topic" in the physics of strongly correlated electron systems with well over 600 publications related to this subject. Presently in 2014 there has been significant progress in combining various experimental results embedded within electronic structure calculations using density functional theory (DFT) to give a consistent description of the itinerant behaviour of the HO transition and its low temperature state. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
108
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 91 publications
3
108
1
Order By: Relevance
“…After almost three decades 1 of intensive experimental and theoretical research, the nature of the ordered phase found in the Kondo system URu 2 Si 2 at temperature below T 0 =17.5 K remains to be unraveled 2,3 . Whereas appearing clearly in the thermodynamic and transport quantities 1,4,5 , the order parameter of this electronic hidden order (HO) state could not be determined by any usual or sophisticated experimental techniques 6 .…”
Section: Introductionmentioning
confidence: 99%
“…After almost three decades 1 of intensive experimental and theoretical research, the nature of the ordered phase found in the Kondo system URu 2 Si 2 at temperature below T 0 =17.5 K remains to be unraveled 2,3 . Whereas appearing clearly in the thermodynamic and transport quantities 1,4,5 , the order parameter of this electronic hidden order (HO) state could not be determined by any usual or sophisticated experimental techniques 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the f-electron intermetallics, URu 2 Si 2 continues to attract interest because it hosts an unidentified ordered state ("hidden order") and unconventional superconductivity at temperatures below T 0 = 17.6 K and T c = 1.5 K, respectively [1][2][3][4][5]. These phenomena occur within a strongly hybridized f-electron lattice that is superficially similar to that of related systems with magnetically ordered ground states [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this parallel, various measurements (e.g., neutron scattering) have revealed that the ordered state does not have an intrinsic magnetic moment [8]. A multitude of theories have been proposed to describe hidden order, where a distinguishing factor is the assumed degree of f-electron localization, but no consensus has been reached regarding their applicability [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of a definitive identification of the symmetries that are broken at the HO transition, the nature of the HO phase remains an outstanding issue in heavy-fermion physics. 35,36 Here, we report an unusual magnetic field dependence of the properties found for a novel phase of the underscreened Anderson lattice (UAL) model 37 that was recently proposed to describe the HO phase of URu 2 Si 2 . The choice of an itinerant model is motivated by the absence of evidence of well-defined crystal field levels in inelastic neutron scattering data 38 and highresolution inelastic X-ray scattering experiments, which indicate that the widths of any crystal field excitations are simply too large to be considered as excitations of a localized system.…”
Section: Introductionmentioning
confidence: 99%